Art in Culinary: What is & What For - Faisal Akbar Zaenal; Hamka Naping; Syamsu Rijal; Yahya; Intan Fauzia Amalia (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2025)
Culinary art represents the creation of food as a product that has been commercialised, and thus operates within the sphere of business. This perspective leads to the understanding that there is an intrinsic connection between culinary experience and commercial kitchen management. In particular, within the realm of culinary artisanship, we argue that this connection emerges from the integration of artistic principles into culinary practice. Consequently, this study centres on defining the meaning and function of art within culinary practice itself. To further explore this connection, we sought to understand how art manifests in culinary practice by passively observing the daily activities of culinary artisans, particularly executive chefs, sous chefs, and pastry chefs, within a brigade de cuisine in hotels and restaurants. Our findings indicate that art in culinary is articulated through three primary aspects: menu and recipe design, haute cuisine, and plating. Collectively, these aspects form the foundation of commercial kitchen management as an essential component of culinary business. This study demonstrates that culinary art extends beyond self-expression, consumer interpretation, and sensory experience. Rather, prior to any form of expression, culinary art functions as a mode of action, an organised set of practices that facilitate the effective orchestration of culinary enterprises through professional kitchen management. Hence, art in culinary embodies the essential competencies required of professional culinary artisans, whose identity is fundamentally defined by professionalism.